Exercise-Based Stroke Rehabilitation: Clinical Considerations Following the COVID-19 Pandemic. (January 2022) - Moncion, Kevin; Rodrigues, Lynden; MacKay-Lyons, Marilyn; Eng, Janice J.; Billinger, Sandra A.; Ploughman, Michelle; Bailey, Damian M.; Trivino, Michael; Bayley, Mark; Thiel, Alexander; Roig, Marc; Tang, Ada
Background . The COVID-19 pandemic attributable to the severe acute respiratory syndrome virus (SARS-CoV-2) has had a significant and continuing impact across all areas of healthcare including stroke. Individuals post-stroke are at high risk for infection, disease severity, and mortality after COVID-19 infection. Exercise stroke rehabilitation programs remain critical for individuals recovering from stroke to mitigate risk factors and morbidity associated with the potential long-term consequences of COVID-19. There is currently no exercise rehabilitation guidance for people post-stroke with a history of COVID-19 infection. Purpose . To (1) review the multi-system pathophysiology of COVID-19 related to stroke and exercise; (2) discuss the multi-system benefits of exercise for individuals post-stroke with suspected or confirmed COVID-19 infection; and (3) provide clinical considerations related to COVID-19 for exercise during stroke rehabilitation. This article is intended for healthcare professionals involved in the implementation of exercise rehabilitation for individuals post-stroke who have suspected or confirmed COVID-19 infection and non-infected individuals who want to receive safe exercise rehabilitation. Results . Our clinical considerations integrate pre-COVID-19 stroke (n = 2) and COVID-19 exercise guidelines for non-stroke populations (athletic [n = 6], pulmonary [n = 1], cardiac [n = 2]), COVID-19 pathophysiology literature, considerations of stroke rehabilitation practices, and exercise physiology principles. A clinical decision-making tool for COVID-19 screening and eligibility for stroke exercise rehabilitation is provided, along with key subjective and physiological measures to guide exercise prescription. Conclusion . We propose that this framework promotes safe exercise programming within stroke rehabilitation for COVID-19 and future infectious disease outbreaks.